An Efficient Approach based on Hierarchal Ontology for Service Discovery in Cloud Computing - Naji Hasan.A.H; Gao Shu; AL-Gabri Malek; Jiang Zi-Long (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
As service providers publish their web services in clouds environment, selecting the most appropriate service among these clouds becomes a very difficult challenge. This paper proposes an efficient approach based on hierarchal ontology to facilitate service discovery in cloud computing. Concepts of services and their relations, which describe services semantically, are distributed in a hierarchal ontology. In addition a matching mechanism for matching these concepts in order to match services in clouds is proposed. The matching results will be evaluated by the QoS of services to select the appropriate service among matched services. A case study is presented to prove the efficiency of our approach. DOI : http://dx.doi.org/10.11591/telkomnika.v12i4.4850